2000
DOI: 10.5771/0949-6181-2000-2-152
|View full text |Cite
|
Sign up to set email alerts
|

Small Slovene Firms and Strategic Information Technology Usage

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Consistent with the findings reported in the literature (Foong, 1999; Levy and Powell, 1997), IS investment is limited to operations and transactions for the 19 SMEs in the control and co‐ordination quadrants. Also, consistent with the literature (Lesjak and Lynn, 2000), these SMEs adopt a low‐cost strategy, with the relationships between their IS and business strategies unchanged. Finally, given that the complexity of the paths to alignment increases substantially from the control to the positioning quadrant, the greatest alignment and highest performance is likely to be achieved by SMEs in the former rather than the latter quadrant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with the findings reported in the literature (Foong, 1999; Levy and Powell, 1997), IS investment is limited to operations and transactions for the 19 SMEs in the control and co‐ordination quadrants. Also, consistent with the literature (Lesjak and Lynn, 2000), these SMEs adopt a low‐cost strategy, with the relationships between their IS and business strategies unchanged. Finally, given that the complexity of the paths to alignment increases substantially from the control to the positioning quadrant, the greatest alignment and highest performance is likely to be achieved by SMEs in the former rather than the latter quadrant.…”
Section: Discussionsupporting
confidence: 83%
“…Second, IS investment is frequently limited to supporting operations and transactions (Foong, 1999; Levy and Powell, 1997). Third, organizations with more sophisticated IS tend to perform less successfully than those with less complex systems (Naylor and Williams, 1994), the greatest alignment and highest performance are reported for systems to improve efficiency (King et al , 2000), and organizations that adopt a low‐cost approach are unlikely to use IS strategically (Lesjak and Lynn, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Business strategies adopted by small firms are found to affect IT use also. Lesjak and Lynn (2000) found owners who pursued a low-cost strategy and saw IS as peripheral to their businesses, due in part to their limited IS knowledge and experience, were less likely to use IS strategically but used IS mostly for efficiency savings. They found that only those SMEs that perceived IS as integral to their business strategy use, due to owner innovativeness and necessity such as in a competitive environment, placed greater emphasis on management information and obtained strategic benefits from IS.…”
Section: Strategic Alignmentmentioning
confidence: 99%
“…Further to these selected strategies, low cost (Lesjak, 2000;Levy et al, 2001;Umble, Haft, & Umble, 2003), innovation Olsen & Saetre, 2007), mobility (Park, 2015), pro-active management (Levy et al, 2001), de-skilled workforce (Azyabi et al, 2014) and customer-centric (Cragg et al, 2002) were also investigated due to its relevance to SMEs as identified by other research. De-skilled workforce are defined as employees who are involved in the performing of certain tasks for which they are not properly trained for (Azyabi et al, 2014).…”
Section: Business Imperatives Of Smesmentioning
confidence: 99%
“…Some SMEs still view investment in software as a cost rather than an investment (Levy et al, 2001). Entities with low cost as a business imperative tend not to use their ISs in a strategic way (Lesjak, 2000) due to the potential costs involved. Small businesses might prefer to buy the basic versions of generic accounting software packages for implementation rather than spending on the more advanced versions or the development/customisation of software.…”
Section: Low Costmentioning
confidence: 99%